2021
DOI: 10.1007/s12020-021-02817-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the level of exercise and hemoglobin A1c in patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: Background: Several systematic reviews and meta-analyses reported that exercise improved hemoglobin A 1 c (HbA 1c ) in patients with type 2 diabetes mellitus, but the improvement reported was heterogeneous. A difference in the level of exercise might be the reason for that heterogeneity.Objective: The aim of study was to evaluate the relationship between changes in HbA 1c and exercise levels when performing various types of exercise.Methods: The inclusion criteria were randomized controlled trials involving ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Physical activity is a component that is reported to be a major determinant in the glycaemic control (Igarashi et al, 2021). For example, interrupting a sedentary lifestyle with 3 min of moderate‐intensity walking or resistance exercise every 30 min improves glycaemic control, including the following night (Dempsey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is a component that is reported to be a major determinant in the glycaemic control (Igarashi et al, 2021). For example, interrupting a sedentary lifestyle with 3 min of moderate‐intensity walking or resistance exercise every 30 min improves glycaemic control, including the following night (Dempsey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Far-reaching scientific proof has revealed how proper and sustained pharmacological management improves the immediate and long-term HRQoL of PLWD [ 12 ]. A recent systematic review and meta-analysis assessing the relationship between the level of exercise and glycosylated hemoglobin (HbA1c) (a measure of long-term glucose control) revealed that HbA1c decreases with exercise [ 13 ]. However, these changes in HbA1c were associated with the overall duration but not the intensity (METs), time (min/session), or frequency (sessions/week) of exercise [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis assessing the relationship between the level of exercise and glycosylated hemoglobin (HbA1c) (a measure of long-term glucose control) revealed that HbA1c decreases with exercise [ 13 ]. However, these changes in HbA1c were associated with the overall duration but not the intensity (METs), time (min/session), or frequency (sessions/week) of exercise [ 13 ]. Therefore, it is imperative to establish the effect of short-term glycemic control and PA on HRQoL from patients´ outcome perspectives.…”
Section: Introductionmentioning
confidence: 99%